Cyclomobility: Perspectives of a moving culture - Araujo , Eloisa Carvalho de; Hidalgo Junior , Jaime Massaguer (Revista Nacional de Gerenciamento de Cidades, 2023)
This article is derived from a research effort associated with the concerns present in many works and practices produced today on the subject of mobility, which highlight the importance that the bicycle has been assuming in society. The debate, when inserted in the appreciation of the culture of cyclomobility, tends to reveal new meanings to the contemporary city and to promote the use of bicycles in Brazilian cities as an expression of a culture in motion. In reproducing the character of descriptive and exploratory research, this Article shares some reflections about the growing impact of cyclomobility in the ways of life of the citizen and in the context of the urban space. And in advancing investigations, the analysis aimed to highlight variations in the theme, with results that problematize and project meanings of the use of bicycles in the urban space, aiming at interpreting current trends. It is expected that the reflections presented here can serve as an incentive to discussions on cyclomobility as a culture in motion, inspiring new research and practices.